A novel approach incorporating Gibbs free energy of mixing to model the environmental impact of industrial brine treatment processes: a case study of hydrometallurgical recycling of lithium-ion batteries - Roelof Frederick Maritz; Guven Akdogan; Christie Dorfling (South African Journal of Chemical Engineering)
The water quality of different industrial effluent streams, produced by various chemical and metallurgical processes, is liable to vary greatly which makes it difficult to compare the environmental impact of unique industrial effluent streams. When performing life cycle assessment studies for chemical processes, researchers are often left using generalised effluent treatment datasets to model their effluent streams. This approach disregards the thermodynamic properties of the effluent streams and only considers the volume of effluent being treated. The aim of this investigation was to develop a simplified, consistent methodology for modelling the environmental impact of unique industrial effluent streams. The proposed method primarily involves calculating the Gibbs free energy of mixing which can then be analysed as either a regular- or a specific energy value, thereby highlighting the importance of both improving effluent quality and reducing effluent quantity to minimise the environmental impact of treating industrial effluent. Subsequently, to approximate the actual energy requirement for treating each individual effluent stream, the Gibbs free energy of mixing may be divided by the exergetic efficiency of the appropriate effluent treatment technology for that specific effluent stream. To illustrate the utilisation of this methodology, a case study was performed which compared the environmental impact of effluent streams produced by different hydrometallurgical lithium-ion battery recycling plants. The process with the lowest specific effluent impact made use of citric acid as leaching reagent in comparison to a more traditional sulphuric acid-based lithium-ion battery recycling process. However, the citric acid-based process had a larger volume of effluent to treat and ultimately required more energy to achieve complete theoretical separation of the contaminants from the effluent than the sulphuric acid-based process.